MERANCANG PERENCANAAN PEMBELAJARAN BERBASIS PENDIDIKAN KARAKTER - Angga Teguh Prastyo (el-hikmah, 2012)
Learning mechanism based on character building is structured in inter-effecting three phases of learning; planning, engagement and evaluation. Lesson plan based on character development comprised of various aspects related with the educational system elected by particular school/madrasah. Therefore, Lesson plan based on character building is employed in all school subjects. There is an interconnection among the school subjects in passing down the values that brings of character education perpetually. It shall not be halted by employment at specific classes. As necessary, school/madrasah may develop the values of character building as pasrt of formal curriculum.